Influence of Carbonyl Iron Particles on the Structural and Mechanical Performance of Magnetorheological Elastomers - Kacuk Cikal Nugroho (Akademi Inovasi Indonesia, 2024)
This study investigates the effects of different types of carbonyl iron particles on the structure and performance of magnetorheological elastomers (MREs). Employing various experimental methodologies, including frequency and strain-dependent testing, the mechanical performance of both anisotropic and isotropic MREs was analyzed. Results indicate that the spatial location of particle chains, frequency, dynamic strain amplitude, and prestrain substantially influence the MREs' mechanical behavior. Special focus was given to the integration of nanoparticles, which significantly enhanced performance metrics. Comparisons were made between MREs based on epoxy, silicone rubber, and polyurethane/Si-rubber hybrids, emphasizing their rheological and morphological properties post-natural weathering in a tropical climate. Additionally, the study highlights the potential applications of MREs in automotive components and sensor technologies, with particular attention to the magnetic and mechanical properties mediated by the inclusion of carbon black and cobalt. The findings provide a comprehensive understanding of the adaptive magnetoelastic characteristics of MREs, contributing to their development and deployment in various smart material applications.